2006
DOI: 10.1111/j.1529-8817.2006.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

EXPLORING THE NATURAL ROLE OF MICROCYSTINS—A REVIEW OF EFFECTS ON PHOTOAUTOTROPHIC ORGANISMS1

Abstract: Cyanobacterial blooms and the production of cyanotoxins represent a serious global problem. Although the effects of a group of important cyanotoxins, microcystins (MCs), have been studied intensively in various organisms, little is known about the natural functions of these cyclic heptapeptides. MCs may have allelopathic effects. This paper summarizes the information from the studies that have investigated the effects of MCs on photoautotrophs in vitro and in vivo. Interactions with terrestrial plants, macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
131
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(134 citation statements)
references
References 100 publications
0
131
1
2
Order By: Relevance
“…The progeny of Swiss Albino mice treated with MCs extracted from cyanobacterial bloom were reported to have a brain size reduction (Babica et al 2006). A sparse structure, distention of endoplasmic reticulum, and swelling mitochondria of cerebrum ultrastructure were shown in the brains of rat offspring after pregnant SD rats were exposed to MC-LR at 10 μg/kg body weight (BW)/day from gestational day 8 (GD8) to postnatal day 15 (PD15) of lactation (Zhao et al 2015a).…”
Section: Neurotoxic Effects Of Mcs Neurostructural Changesmentioning
confidence: 99%
“…The progeny of Swiss Albino mice treated with MCs extracted from cyanobacterial bloom were reported to have a brain size reduction (Babica et al 2006). A sparse structure, distention of endoplasmic reticulum, and swelling mitochondria of cerebrum ultrastructure were shown in the brains of rat offspring after pregnant SD rats were exposed to MC-LR at 10 μg/kg body weight (BW)/day from gestational day 8 (GD8) to postnatal day 15 (PD15) of lactation (Zhao et al 2015a).…”
Section: Neurotoxic Effects Of Mcs Neurostructural Changesmentioning
confidence: 99%
“…Among the toxic cyanobacteria, M. aeruginosa commonly occurs in highly eutrophic lakes, and it often dominates the phytoplankton in eutrophic lakes and ponds (Yamamoto & Nakahara 2009). Microcystis aeruginosa produces the hepatotoxin microcystin, which is a threat to human and environmental health (Babica et al 2006). Recently, it has been reported that M. aeruginosa NIES 843 and PCC 7806 harbour genes for PCD that may be related to the rapid collapse of Microcystis blooms (Kaneko et al 2007;Frangeul et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the production of toxic metabolites is suspected to alter biotic communities through allelopathic interactions. Several hypotheses have been proposed concerning the role of such metabolites at several trophic levels (for reviews, see Vasconcelos and Pereira, 2001;Gross, 2003;Wiegand and Pflugmacher, 2005;Babica et al, 2006;Leflaive and TenHage, 2007;Schatz et al, 2007). However, such a toxic activity is difficult to characterize because of (i) the presence of other molecules that may modify the effect of toxins (Rohrlack et al, 1999b;Buryskova et al, 2006), (ii) the adaptation of target organisms (Wilson and Hay, 2007) and (iii) the appearance of avoidance behaviour in some species of zooplankton (Kurmayer and Ju¨ttner, 1999).…”
Section: Introductionmentioning
confidence: 99%